Chemical Composition and Mixing State of Fine Particles during Haze Periods in Yinchuan - Kangning Li; Yanqiu Ma; Liukun Li; Bin Huang (Aerosol and Air Quality Research)
Abstract In this study, we explored the chemical composition and mixing state of fine atmospheric particles in Yinchuan between December 21 and 31, 2021. For this, the single-particle aerosol mass spectrometry (SPAMS) technique was used. Black carbon particles were found to be the predominant aerosol type (in terms of number fraction) throughout the sampling period, accounting for 61.15% of all sampled particles. Considerable changes were noted in the mixing state of the fine particles in the study area. Furthermore, prominent mass spectrum characteristics of potassium particles were observed. The 39K+ signal in the positive mass spectrum was stronger than the other signals. Throughout the sampling process, K-rich and potassium-elemental carbon (KEC) particles accounted for 25.86% and 13.05% of all sampled particles, respectively, followed by OC and NaKEC, which accounted for 12.32% and 11.45%, respectively. With time, complex processes of aerosol concentration variation detected by SPAMS were observed. The number fractions of elemental carbon/organic carbon (ECOC) and KEC particles were significantly higher on polluted days than on clean days. ECOC and KEC particles were more mixed with sulfate and nitrate than EC and NaKEC particles. Compared with clean days, the particle size of each BC particle increased on polluted days. Furthermore, ECOC and KEC particles had larger particle sizes and stronger sulfate and nitrate signals than EC and NaKEC particles, which indicates that ECOC and KEC particles were mostly formed during the aging process. Local pollution events were associated with primary combustion emission and secondary particle generation.